Electronic conduction processes in VCM-type metal-oxide ReRAM cells - Rosário, Carlos Miguel Marques do (2021)
New applications, such as neuromorphic computing, and the limitations of current semiconductor technologies demand a revolution in electronic devices. As one of the key enablers of a new electronics paradigm, redox-based resistive switching random access memory (ReRAM) has been the focus of much research and development. Among the ReRAM research community, Ta2O5 has emerged as one of the most popular materials, for enabling high endurance and high switching speed. Ta2O5-based ReRAM rely on the nonvolatile change of the resistance via the modulation of the oxygen content in conductive filaments, as it is described in the valence change mechanism. However, the filaments’ structure and exact composition are currently under intense debate, which hinders the development of better device design rules. The two current models in the literature consider filaments composed of oxygen vacancies and those containing metallic Ta. This work attempts to solve this dispute by reporting a detailed study of the electrical transport through the conductive filaments inside Ta2O5-based ReRAM. In parallel, the electrical transport and structure of substoichiometric TaOx thin films, grown to try and match the material of the filaments, was studied in detail. A strong correlation between the transport mechanisms in the conductive filaments inside the Ta2O5 ReRAM and in the TaOx thin films with x 1 was found. This clearly links the physical properties of the materials composing the filaments and the substoichiometric TaOx thin films. Structural analysis performed on the TaOx films reveals the presence of Ta clusters inside the films. Moreover, the electrical transport of metallic Ta films shows the same transport mechanism as TaOx with x 1, for most of the measured temperature range, from 2 K to 300 K. Beyond the transport mechanisms, both cases share a carrier concentration on the order of 1022 cm−3 and a positive magnetoresistance associated with weak antilocalization at T < 30 K. Therefore, it is concluded that the transport in the TaOx films with x 1 is dominated by a percolation chain of Ta clusters embedded in an insulating Ta2O5 matrix. These clusters exhibit disordered metal-like behaviour, where quantum corrections to the Boltzmann transport dominate the conduction. In conclusion, the electrical transport in the conductive filaments inside Ta2O5-based ReRAM devices is determined by percolation through Ta clusters, which is in line with independent observations of metallic Ta in the filaments. This work strongly supports the metallic Ta filament model.